Технологія натуральних ароматизаторів орієнтованих на вітчизняну сировинну і апаратурну базу - Фролова, Н. Е.; Силка, І. М. (НТУ "ХПІ", 2015)
Проведено наукові і практичні дослідження технології, яка впроваджує фракційну вакуумну дистиляцію в переробку ефірних олій, що дозволяє отримати серію натуральних харчових ароматизаторів з однієї ефірної олії. З'ясовано технологічні стадії, встановлено параметри процесів, визначено якісні показники готових ароматизаторів. Розроблено апаратурно-технологічну схему виробництва натуральних ароматизаторів, а також рецептури ароматизаторів для внесення в харчові продукти.

Food flavors began to produce industrial way only in the XX-th century. Flavours improve the flavor, the assimilation of products and expand the assortment products of the same type. Natural flavors are especially in demand. They are represented in the Ukrainian market poorly. Essential oils belong to the natural flavor, too. Essential-oil industry of Ukraine works more for export. There are many solutions of essential oils recycling, for example, distillation, extraction, liquid gases, membrane technology and others. The purpose of this work is the study of technological stages ofproduction of natural flavorings of local essential oils.
Technology of natural flavours from home raw material and apparatus base
Keywords: ефірна олія; коріандр; фракціонування; essential oil; coriander; fractionation technology